Nanoindentation Experimental Study on Mechanical Properties of As-cast BNi-2 Solder Alloy. (2015) - Chen, D.Q.; Zhou, G.-Y.; Liu, Z.P.; Tu, S.-T.
Abstract: Nanoindentation testing has been used to study mechanical properties of as-cast BNi-2 solder alloy. Hardness and modulus were measured by the nanoindentation experiments. It is confirmed that it is loading rates insensitive to as-cast BNi-2 filler metal from the elasto-plastic nanoindentation responses. In this study, indentation size effect has been discussed. It is found that as-cast BNi-2 is independent of the indentation size effect. Using the model proposed by Dao et al., the yield strength and work hardening exponent were regressed from the loading–unloading behavior during indentation. The purpose of the present work is to obtain a comprehensive elastic–plastic properties understanding of as-cast BNi-2 filler metal which can be better application for engineering.